Posted by
**Margie** on
.

Use the Substitution method to solve the system of equations.

y - 2x = -5

3y - x = 5

Solve one of the equations for x or y.

Let's solve the first one for y:

y - 2x = -5

y = 2x - 5

Now let's substitute 2x - 5 for y in the second equation to solve for x:

3(2x - 5) - x = 5

6x - 15 - x = 5

5x - 15 = 5

5x = 20

x = 4

Substitute 4 for x in either equation to solve for y. Let's choose the first one.

y - 2(4) = -5

y - 8 = -5

y = 3

There you have it! Check the solution with both equations to make sure we have the right solutions. It always helps to check your work!

I hope this will help.